ANALISIS MARKTING MIX UNTUK MENINGKATKAN VOLUME PENJUALAN PADA RAFIJAYA FOTOKOPI DI KOTA MEDAN - Putri Sepfiani; Zuhrinal M. Nawawi (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
Economic development resulted in increasingly fierce competition in business. To be able to survive and win in competition, a marketing strategy is needed. One of them is the marketing mix using the 4P components, product, price, promotion and place. This research aims to examine and understand whether Rafijaya Fotocopy can apply a marketing mix strategy to affect sales. This study uses a qualitative approach in order to clearly describe sales activities at Rafijaya Fotocopy. Using descriptive data analysis techniques, with data collection techniques namely observation and interviews. Based on the results of research on Rafijaya Photocopy, the marketing mix is ​​applied where the 4P components, product, price, promotion and place have an influence on increasing sales volume.